2002
DOI: 10.1088/0953-8984/14/14/307
|View full text |Cite
|
Sign up to set email alerts
|

The Fermi level in diamond

Abstract: Diamond is a wide-band-gap material with large donor and acceptor ionization energies. In principle, at room temperature and below, the Fermi energy is pinned close to the donor or acceptor level, depending on which is present in the higher concentration. In semiconductors with shallow donors and acceptors the equilibrium charge states of defects are determined by the position of the Fermi level. However, in an insulating material like diamond we show that the calculated position of the Fermi level does not n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
92
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 25 publications
1
92
0
3
Order By: Relevance
“…25 In some cases, NV 0 is more stable than NV − , which we attribute to the presence of additional defects that are more stable with an additional electron than the NV center. 26 Laser light may decharge the NV − form of the NV center by causing the transition to the 3 E and 1 E excitations with configuration u 2 v 2 e 1 w N 1 in the doped clusters: the extra electron gets transported to a nearby nitrogen donor.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…25 In some cases, NV 0 is more stable than NV − , which we attribute to the presence of additional defects that are more stable with an additional electron than the NV center. 26 Laser light may decharge the NV − form of the NV center by causing the transition to the 3 E and 1 E excitations with configuration u 2 v 2 e 1 w N 1 in the doped clusters: the extra electron gets transported to a nearby nitrogen donor.…”
Section: Resultsmentioning
confidence: 80%
“…Collins 25 suggested that electrons in diamond defects are not in thermal equilibrium, so the mechanism for decharging and charging the NV center is of interest. Direct electron tunneling is unlikely to be the mechanism unless the nitrogen to NV center distance is short: the ͗w N ͉H͉e X,Y ͘ molecular orbital matrix element exponentially drops with distance.…”
Section: Resultsmentioning
confidence: 99%
“…The charged state of an NV center depends on the NV −/0 transition level relative to the Fermi level. In diamond doped with nitrogen, the Fermi level is 1.7 eV below the conduction band minimum (CBM) [56,57] , and the NV − level is 2.58 eV below the CBM [58,59]. Thus, in free-standing nitrogen-doped diamond, the NV centers deep in the bulk diamond are likely to be in the NV − state (NV 1 in Fig.…”
Section: B Stability Of Shallow Nv − Centersmentioning
confidence: 99%
“…5a). However, the NV − charged state can be stabilized by controlling the Fermi level and the band bending near the interface via electrical gating [49,[61][62][63], chemical treatment [56,60,64], or by controlling the charge/discharge process by optical excitation [65][66][67], and possibly a combination of the above operations. For example, diamond with PEA oxygen-terminated surface can stabilize shallow NV − centers [60,68].…”
Section: B Stability Of Shallow Nv − Centersmentioning
confidence: 99%
“…In the experiments, the NV center ensembles are produced by high dosage (10 13 cm −2 ) nitrogen ion implantation. However, nitrogen defect, as donor of electron [33][34][35] , could change the level structure in diamond 36,37 . Therefore, high dosage ion implantation might change the charge state conversion process of NV center, which will subsequently affect the results of CSD nanoscopy.…”
mentioning
confidence: 99%